Superheating and Homogeneous Single Bubble Nucleation in a Solid-State Nanopore - Nagashima, Gaku (2014)
We demonstrate extreme superheating and single bubble nucleation in an electrolyte solution within a nanopore in a thin silicon nitride membrane. The high temperatures are achieved by Joule heating from a highly focused ionic current induced to flow through the pore by modest voltage biases. Conductance, nucleation, and bubble evolution are monitored electronically and optically. Temperatures near the thermodynamic limit of superheat are achieved just before bubble nucleation with the system at atmospheric pressure. Bubble nucleation is homogeneous and highly reproducible. This nanopore approach more generally suggests broad application to the excitation, detection, and characterization of highly metastable states of matter.